Gout in China, 1990–2017: the Global Burden of Disease Study 2017. (February 2021) - Tang, Y.M.; Zhang, L.; Zhu, S.Z.; Pan, J.J.; Zhou, S.H.; He, T.J.; Li, Q.
Abstract: Objective: The aim of the study was to estimate the gout burden and risk factors in China from 1990 to 2017. Study design: The Global Burden of Disease (GBD) Study uses various analytical tools and a diverse set of data sources to generate comparable estimates of deaths and mortality rates broken down by age, sex, cause, year, and geography. Methods: We used the results from the GBD Study 2017 to compare disability-adjusted life years (DALYs), prevalence, incidence, and risk factors of gout in China. The median of the percentage change and 95% uncertainty intervals were determined for the period between 1990 and 2017. Results: The age-standardized DALY rate, prevalence, and incidence increased 6.92%, 6.88%, and 6.16%, respectively, in China from 1990 to 2017. Although the rates of gout both globally and in China were increasing, the range of change for males in China was larger than that of the global level. All risk factors combined accounted for 30.04% of gout DALYs in 2017. The leading risk factors for gout DALYs were high body mass index and impaired kidney function, and the proportion of high body mass index increased significantly from 10.67% to 24.31%, whereas the proportion of impaired kidney function remained basically unchanged. Conclusions: The age-standardized DALY rate, prevalence, and incidence in China have increased progressively since 1990. Increasing attention on body weight management should be prioritized for controlling the rising prevalence of gout in the young and middle-aged population. Highlights: This is a comprehensive overview of the epidemiological situation and trends regarding the gout burden in China from 1990 to 2017. The age-standardized disability-adjusted life year rate, prevalence, and incidence in China have increased progressively since 1990. Increasing attention on body weight management should be prioritized in the young and middle-aged population.